Authority of administrative Judiciary toward decisions that have the force of law in Iraq and the Kurdistan Region - Jumha qadir salih; Nahro Asaad Abdulla (QALAAI ZANIST SCIENTIFIC JOURNAL, 2020)
The purpose of this research is to study the decisions that the legislative authority entrusts with the executive authority to issue and which has the force of law in exceptional circumstances to which the state is exposed to assure the proper functioning and continuity of state organs, and to protect security and state safety from internal and external threats to the sovereignty of the state and its members. And the seriousness of these decisions on the rights and freedom of the individual and society, and highlight the limits of the authority of the administrative Judiciary over these decisions. This research contains two topics: The first section is devoted to the definition of decisions that have the force of law with the legal basis on which these decisions are based. The second research is devoted to talk about the authority of the Administrative Judiciary in both Iraq and the Kurdistan Region - Iraq over decisions that have the force of law. At the end of this research, the researchers reached some of the most important results: the decisions that have the force of law issued by the political and executive authority in the case of the country's exposure to internal and external risks, and that these decisions have adverse effects on the rights and freedoms of individuals organized by law, narrow the limits of the administrative Judiciary authority In resolving the issues resulting from these decisions.